The Effect of Superior’s Reputation and the Need for Achievement Character on Budgetary Slack: An Experimental Study - Fitri Romadhon; Alfiana Fitri; Husnunnida Maharani; Niluh Putu Dian Rosalina Handayani Narsa (Universitas Pendidikan Ganesha, 2022)
The purpose of this study is to examine the role of the superior's reputation and the character of subordinates referred to as need for achievement (NFA) toward budgetary slack. We employed experimental method with a factorial design of 2 (superior reputation) x 2 (need for achievement). Hypothesis testing was conducted using two-way ANOVA. By using as many as 78 accounting and management students as experimental participants, t he results prove that subordinates who have superiors with favorable reputations tend to create a lower slack than those who have superiors with unfavorable reputations. Meanwhile, if a subordinate has a high need for achievement character, then the subordinate will tend to create a higher budgetary slack. Further, this study shows that budgetary slack tends to be created by subordinates with high need for achievement characters can be lowered if they get a favorable superior than an unfavorable one.